Using Blended Learning Strategies to Address Teaching Development Needs: How Does Canada Compare? - Kanuka, Heather; Rourke, Liam (Canadian Journal of Higher Education, 2013)
The provision of blended learning strategies designed to assist academics in the higher education sector with the knowledge, skills, and abilities required for effective teaching with technology has been, and continues to be, a challenge for teaching centres in Canada. It is unclear, first, whether this is an ongoing issue unique to Canada; and, second, if it is not unique to Canada, whether we might be able to implement different and/or more effective strategies based on what others outside Canada are doing. Teaching centre leaders in Australia, Finland, Sweden, Denmark, Britain, Scotland, and the United States (n=31) were interviewed to explore how their units used blended learning strategies. Findings suggest that, as in Canada, there is a “value gap” between academics and leaders of teaching centres regarding teaching development initiatives using blended learning strategies.